Risk Management: Can it be a Panacea for State-Owned Enterprises Ills? - Chauke, K. R. (International Conference on Public Administration and Development Alternatives (IPADA), 2018)
There is a requirement in terms of King IV code of good practice that the directors should disclose their role on the risk oversight function of an entity, this disclosure should be covered in the annual financial statements. The board’s oversight role on risk functions includes amongst others, how the risk function is administered as well as the impact that such oversight role has on the entity’s processes. What could be the impact of failure in the oversight role and what are the contributors of such failure in the performance of such oversight role. The failure of boards and individual directors that is experienced in the state-owned enterprises, what could be the contributing factor or factors to such failures, can it be attributed to their laxity in the implementation of risk management programs or is there any other cause? The paper will review the background on risk management function and its attendant programs. Also, the wider duties of directors of state owned enterprises and their duties will be briefly analysed before a coming to any conclusion that can be made that could enable and capacitate directors in the implementation of risk management programs. The relationship will be drawn between the successes and failures in the implementation of risk management programs and the failure of boards in the state-owned enterprises. The article will show that risk management programs can play an important role in performance of fiduciary duty of directors in the state-owned enterprises as is the case in the private sector. It will further indicate the consequences on the director who fails in carrying out this fiduciary duty of proper performance of the oversight role on risk management.
Journal article published in the International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: Directors; Disclosure; Risk; State owned enterprise; Financial risk management